HUBUNGAN FILOGENETIK SPESIES LIMNONECTES (RANIDAE: AMPHIBIA) ASAL SUMATERA BARAT DAN ASAL ASIA TENGGARA BERDASARKAN GEN 16S RIBOSOMAL RNA - Tjong, Djong Hon; Iskandar, Djoko T.; Gusman, David (Makara Journal of Science, 2010)
Phylogentic Relationship among Limnonectes (Ranidae: Amphibia) found in West Sumatra with Other Species from South East Asia based on the based on the 16S rRNA Gen. The objective of this research was to study the phylogenetic relationship among Limnonectes species found in West Sumatra and with other species from South East Asia based on the partial DNA sequences16S rRNA sequences. DNA sequences were aligned using ClustalX version 1.64b, and the phylogenetic relationship within samples were analyzed using PHYLIP version 3.5c program. The alignment showed that, from 805 sites, there are 250 parsimony informative polymorphism sites. The phylogenetic tree showed that all of the Limnonectes spesies were divided in two clusters, the L. blythii complex and L. kuhlii complex. L. kuhlii and L. sp1 clustered into L. kuhlii complex and L. shomponerum and L. macrodon were clustered to L. blythii complex. This result showed that L. kuhlii and L. blythii are species complexes that are actually constituted of several species.